Hip arthroscopy in the high-level athlete: Does capsular closure make a difference? - Hassebrock, J. D.; Makovicka, J. L.; Chhabra, A.; Anastasi, M. B.; Menzer, H. M.; Wilcox, J. G.; Economopoulos, K. J. (The American Journal of Sports Medicine)
Background: Hip arthroscopy has been shown to be effective in athletes who have femoral acetabular impingement and labral tearing. The effect of complete capsular closure versus nonclosure on return to play is unknown.